AVALIAÇÃO DA ATIVIDADE ANTIOXIDANE E FOTOPROTETORA DO MESOCARPO DE BABAÇU (Attalea speciosa) - LIMA, Mércia Machado Araújo (2023)
Sunscreens are an option to avoid photodamage, but they have shown side effects such as skin absorption and toxic metabolites, and natural photoprotectors are an alternative to this problem given their low toxicity. This study maintains this focus with the evaluation of the antioxidant and photoprotective activity of babassu mesocarp (Atallea speciosa). Aqueous extract (EAB) and hydroalcoholic extract (EHB) were prepared, submitted to in vitro tests, with the determination of phenolic compounds using Folin Cicateau and antioxidant activity by DPPH radical and ABTS, for dosage of proanthocyanidins Vanillin and HCl were used. The sun protection factor (SPF) was obtained according to the Mansur reaction (1986), while for the analysis of the chemical composition High Performance Liquid Chromatography (HPLC) was used, concluding the analyzes with the cytotoxicity test. EHB obtained relevant results in the phytochemical and SPF analyses, being used in HPLC and Cytotoxicity, detecting epicatechins and proanthocyanidins, in addition to considerable safe cell viability, respectively. This work demonstrated important antioxidant and photoprotective activity of babassu mesocarp, but further studies of chemical characterization and stability are needed, as this resource constitutes a good option for the formulation of safer and more efficient photoprotectors.